Examining the Societal Impact on Women Involved in Income Generation - Karki, Sabita (International Research Journal of MMC, 2024)
Nepal has taken significant steps towards gender equality in recent years and has a relatively high percentage of women participating in the labor force. However, a study has found that a large number of economically active women in Nepal do not have access to economic resources, with three-quarters of the unpaid family labor force being women. This study aims to examine how societal factors influence women’s participation on income-generating activities and identify with a sample of 50 women selected from Kathmandu valley through a convenience sampling technique. The data were collected through survey methods using questionnaires. Data analysis was done using "SPSS" and Ms-Excel software, with correlation and regression analyses being conducted to determine the relationship between variables and the percentage change in one variable due to the change in another variable. The study concludes that societal factors have a positive impact on women’s involvement in income-generating activities in the Kathmandu area. The R and R square were .83 and .68, respectively. The research offers insights into the transformation of societal attitudes and norms. It enriches the academic discourse by supplying empirical data on how societal influences affect women’s economic engagement, contextualized within a distinct cultural and geographical setting.